FEATURES OF ENSURING THE FINANCIAL STABILITY OF UKRAINIAN COMPANIES DURING THE CRISIS - SKOROPAD, Iryna; LAZAREV, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Aspects of the current state and problems of restoring the financial and economic state of Ukrainian enterprises in the conditions of a crisis caused by a full-scale war are analyzed. The purpose of the article is to identify the peculiarities of ensuring the financial stability of Ukrainian enterprises in crisis conditions. The war, which began in February 2022, significantly complicated the environment for the functioning and development of Ukrainian business. Such large-scale changes naturally led to the washing out of working capital of enterprises and deterioration of their financial and economic condition. The above-mentioned problems intensified the relevance of the issue of restoring the financial stability of domestic business in the conditions of war and crisis. It is proven that the financial and economic condition of domestic enterprises in the conditions of the war and the critical instability created by it significantly worsened. It is shown that these trends led to a decrease in the level of financial stability of economic entities, which continues to deteriorate. It was concluded that this is negative, because it leads to a deterioration of investment attractiveness, creditworthiness and the ability of Ukrainian enterprises to maintain economic security and function as such. Analyzed and indicated the trends leading to the deterioration of the financial stability of domestic business, namely, the decrease in profit margins (increasing negative financial results), the decrease in the level of profitability and the increase in the number and share of unprofitable enterprises in the real sector of the national economy of Ukraine, in particular industrial. It is argued that in order to restore and further strengthen the position in terms of strengthening the sustainability of domestic business entities, effective measures should be implemented in the following areas: (1) increase in equity; (2) optimization of the volume and terms of use of the capital involved in the business; (3) increasing the efficiency of management and directing profit growth to the means of improving the financial and economic condition, strengthening the financial stability of corporate structures.